TRACE ELEMENTS HOMEOSTATIC IMBALANCE IN MILD AND SEVERE PSORIASIS: A NEW INSIGHT IN BIOMARKER DIAGNOSTIC VALUE FOR PSORIASIS - Nagat Sobhy Mohamad (Our Dermatology Online, 2013)
Introduction: The pathogenesis of psoriasis remains elusive and is a subject of interest to clinicians and scientists. Many studies have thrown light on the etiopathogenesis of psoriasis at both molecular and tissue concentrations. Of these, the role of trace metals has been of interest. Objective: To evaluate the possible role of trace elements in mild and severe psoriasis. Patients: Sixty patients suffering from psoriasis were included in the study and 30 healthy subject served as a control. Methods: Serum sample analysis for some trace elements namely Na, K, Ca, P, Cu, Zn, and Fe using inductively coupled plasma-atomic emission spectroscopy (ICP-AES). In psoriatic patients and control, the severity of psoriasis was assessed by psoriasis area severity score (PASI score). Results: In psoriatic patients the level of serum calcium and zinc were diminished while the level of serum copper, iron and organic phosphorous were increased. These changes were significantly evident in severe psoriasis compared to control and mild psoriasis (P<0.05). Conclusions: There may be a role for trace elements in the etiopathogenesis of psoriasis.